2018
DOI: 10.1186/s12879-018-3611-x
|View full text |Cite
|
Sign up to set email alerts
|

Find the right sample: A study on the versatility of saliva and urine samples for the diagnosis of emerging viruses

Abstract: BackgroundThe emergence of different viral infections during the last decades like dengue, West Nile, SARS, chikungunya, MERS-CoV, Ebola, Zika and Yellow Fever raised some questions on quickness and reliability of laboratory diagnostic tests for verification of suspected cases. Since sampling of blood requires medically trained personal and comprises some risks for the patient as well as for the health care personal, the sampling by non-invasive methods (e.g. saliva and/ or urine) might be a very valuable alte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
63
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(68 citation statements)
references
References 165 publications
(137 reference statements)
2
63
0
3
Order By: Relevance
“…These results reinforce the diagnosis algorithm described for WNV where the viremia of the WNV infection is relatively short (viral RNA can be detected in serum samples only around 7 dpo) but in urine samples viral RNA can be detected for a longer period and in higher copy numbers. This result has been observed before in several studies, in fact some of them have revealed the long persistence of WNV in urine particularly in patients with WN fever compared to patients with WN neuroinvasive disease, which had a higher viremia for a shorter period than those with WN fever [25]. Whether urine samples are a useful source for surveillance studies for WNV distribution and for analyzing the severity of the disease in patients with neuroinvasive and/or kidney manifestation needs to be investigated.…”
Section: Resultssupporting
confidence: 61%
“…These results reinforce the diagnosis algorithm described for WNV where the viremia of the WNV infection is relatively short (viral RNA can be detected in serum samples only around 7 dpo) but in urine samples viral RNA can be detected for a longer period and in higher copy numbers. This result has been observed before in several studies, in fact some of them have revealed the long persistence of WNV in urine particularly in patients with WN fever compared to patients with WN neuroinvasive disease, which had a higher viremia for a shorter period than those with WN fever [25]. Whether urine samples are a useful source for surveillance studies for WNV distribution and for analyzing the severity of the disease in patients with neuroinvasive and/or kidney manifestation needs to be investigated.…”
Section: Resultssupporting
confidence: 61%
“…In addition, small-scale studies have already shown the potential for using metagenomic sequencing of sewage extracts for the detection of a range of virus families 18 20 (Table 1 in Appendix). While these studies have largely focused on viruses with a replication phase in the gastro-intestinal tract, the fecal and/or urinary shedding of, for instance, measles virus, yellow fever virus, Zika virus, West Nile virus, Ebola virus, SARS coronavirus, and MERS coronavirus suggests the potential utility of sewage testing to capture circulation of these pathogens as well 21 25 . Moreover, metagenomic sequencing has the potential to detect any viral genomic material in the sample, without targeting a specific viral pathogen or limiting for only known viral pathogens.…”
Section: Introductionmentioning
confidence: 99%
“…In a review of over 700 publications on diagnostic approaches of viral infections, the authors observed that the application of non-invasive sampling methods such as the use of saliva for diagnosis and monitoring of viral diseases need to be widely investigated 33 . This is particularly critical for respiratory infections such as SARS-CoV-2, in which the viral load in saliva has been shown to be higher in early phase of the disease 31,32,34 .…”
Section: Discussionmentioning
confidence: 99%